Histamine Poisoning from Ingestion of Fish or Scombroid Syndrome. (7th December 2014) - Tortorella, Vincenzo; Masciari, Peppino; Pezzi, Mario; Mola, Assunta; Tiburzi, Simona Paola; Zinzi, Maria Concetta; Scozzafava, Annamaria; Verre, Mario
Abstract : The scombroid poisoning is due to the ingestion of poorly preserved fish (especially tuna, sardines, and mackerel) out of the cold chain. Under the influence of the proliferation of gram negative bacteria that occurs for heating, the histidine content in the muscle of the fish is converted into histamine, by the action of the enzyme histidine decarboxylase. If the histamine is ingested in large quantities, it causes an anaphylactoid reaction with a variety of symptoms from moderate to severe to life-threating. We will describe two cases that came under our observation after consuming a meal of bluefin tuna. The diagnosis of scombroid syndrome was made on the basis of the anamnestic data and the clinical one. The rapid resolution of the signs and symptoms after treatment with histamines H1-H2 receptor blockers confirmed the suspected diagnosis.